Editorial: From History to Infrastructure - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2023)
This editorial comes in three parts: encouragement to delve into the start of long-distance telecommunications in Australia; some remarks on telecommunications as infrastructure; and a brief introduction to the papers in this issue.